Acanthosis nigricans and its association with cardio-metabolic risk factors in children with overweight/obesity: A school-based cross-sectional study - Rashmi R. Das; Manaswini Mangaraj; Saurav Nayak; Amit K. Satapathy; Samarendra Mahapatro (Journal of Family Medicine and Primary Care)
Background: Acanthosis nigricans (AN) is a common finding often associated with hyperinsulinemia and childhood obesity. There has been a lack of studies evaluating the association of AN with underlying cardio-metabolic risk factors in children and adolescents. Our objective was to study the association between AN and cardio-metabolic risk factors in children with overweight/obesity. Methods: This cross-sectional study included school-going children (6–16 years of age) with overweight/obesity. Physical examination, anthropometry, and blood pressure (BP) data were collected. Fasting blood samples were collected to measure insulin, glucose, homeostasis model assessment index (HOMAIR), and lipid profile. Results: Of 1930 children screened, 545 had overweight/obesity, and were included. Boys to girls ratio was 1.27. AN was present in 46.4% of children. Children with AN had higher body mass index [BMI] (P < 0.01), waist circumference [WC] (P < 0.01), systolic (P = 0.03), and diastolic BP (P = 0.02), hyperglycemia (P = 0.02), hyperinsulinemia (P < 0.01), and a higher HOMA-IR (P < 0.01) compared to those without AN. HDL level was lower in children with AN. Conclusions: Children with overweight/obesity who have AN have significant elevations of BP, insulin level, and HOMA-IR. AN is a clinical marker that seems to be associated with cardio-metabolic risk factors in children with overweight/obesity in the given study population.